Simulation of increasing night temperature on vegetative and generative of paddy (Oryza sativa L.) - D F Putra; S Y Tyasmoro; K P Wicaksono; L Vincie (Journal of Degraded and Mining Lands Management, 2015)
The rate of respiration increases with increasing temperature. It causes a problem to occur with photosynthesis result (photosynthate) generated during photosynthesis as a source of energy for metabolism of plants. The objective of this study was to evaluate of growth and the production result by affected an increasing night temperature on paddy. The simulation was performed in growth chamber with increased night temperature by 20 C (T1) and 40 C (T2) higher than normal night temperature (T0). Growth phase of rice plant treated an increase in night temperature among others on the vegetative phases continues on the generative phase (VG), was treated only on the vegetative phase (V) and treated only on the generative phase (G). The number of tillers, leaf area, number of leaf, the total dry weight of rice plant on the T2 had values that were lower than at T0 and T1. The decreased values in the parameter number of tillers, leaf area, number of leaf, and total dry weight at the end of the observation were observed on T2V and T2 VG. The T2 had longer panicle than T1 and T0, but the number of panicle, weight of  seedper plant, harvest index (HI), the number of productive tillers, flowering time, harvesting time , nitrogen content in the leaves, the and percentage of open stomata values were lower than T1 and T0.  T1G, T1VG, T2VG and T2G showed lower percentage of full grain than at T0. T1 and T2 treatments on VG and V resulted in the delay of flowering time. T1 and T2 on the VG phase resulted in the delay of harvesting time.